Who we are and how we got here : ancient DNA and the new science of the human past - Reich, David (Oxford : Oxford University Press, 2018)
David Reich describes how the revolution in the ability to sequence ancient DNA has changed our understanding of the deep human past. This book tells the emerging story of our often surprising ancestry - the extraordinary ancient migrations and mixtures of populations that have made us who we are.
Introduction -- Part one: The deep history of our species (1. How the genome explains who we are ; 2. Encounters with Neanderthals ; 3. Ancient DNA opens the floodgates) -- Part two: How we got to where we are today (4. Huamnity's ghosts ; 5. The making of modern Europe ; 6. The collision that formed India ; 7. In search of Native American ancestors ; 8. The genomic origins of East Asians ; 9. Rejoining Africa to the human story) -- Part three: The disruptive genome (10. The genomics of inequality ; 11. The genomics of race and identity ; 12. The future of ancient DNA)
Includes bibliographical references (pages 287-320) and index.
Keywords: Human genetics; Genomics; DNA -- Analysis; Prehistoric peoples; Human population genetics